Socialization of a Land Rent as a Way of Reconstruction of Social Structure for the Benefit of Ensuring Cost Efficiency - O. A. Аntoncheva; T. E. Apanasenko (Управленческое консультирование, 2019)
The revolution proclaimed, inter alia, to transfer the ownership of land to those who worked on it for their own benefit. Still, even in theory, it was yet to be defined what kind of ownership was needed to meet its primary objective.It is always troublesome, when a capitalizable object is transformed into a public asset because in the context of the surplus product situation, no mechanism of such transformation has ever been developed. Nevertheless, soviet socialism achieved some progress in a more specific issue of transforming land into a public asset via socialized land rent, in particular, via a differential land rent. In the socialist time, an absolute land rent was challenged by the non-match between socialist monopoly and monopoly in terms of classical political economy as a source of absolute rent; lack of clear distinction between rent and profit on capital where there are no restrictions on capital overflow between economy sectors thus, rendering absolute rent literally non-existent in Pareto terms.Since the end of socialism, the egalitarian process has lost its gain of a socialized differential land rent and had to look for other options, this time in the new situation of private land ownership. This brings us to the works of Henry Georges where he suggests replacing taxes by land rent. Thereby socialization of a land rent from the instrument of elimination of social inequality will be transformed to the tool of economic efficiency.